Predictive Value of Pretreatment Lymphocyte-to-Monocyte Ratio and Platelet-to-Lymphocyte Ratio in the Survival of Nasopharyngeal Carcinoma Patients - Chen Y (Dove Medical Press, 2021)
Yibiao Chen,1,2 Jianda Sun,1,2 Dan Hu,1,2 Jian Zhang,1,2 Yuyun Xu,1,2 Huiting Feng,1,2 Zhijie Chen,1,2 Yi Luo,1,2 Yunlong Lou,2,3 Heming Wu2,4 1Department of Radiation Oncology, Meizhou People’s Hospital (Huangtang Hospital), Meizhou Academy of Medical Sciences, Meizhou, People’s Republic of China; 2Guangdong Provincial Key Laboratory of Precision Medicine and Clinical Translational Research of Hakka Population, Meizhou People’s Hospital (Huangtang Hospital), Meizhou Academy of Medical Sciences, Meizhou, People’s Republic of China; 3Department of Nuclear Medicine, Meizhou People’s Hospital (Huangtang Hospital), Meizhou Academy of Medical Sciences, Meizhou, People’s Republic of China; 4Center for Precision Medicine, Meizhou People’s Hospital (Huangtang Hospital), Meizhou Academy of Medical Sciences, Meizhou, People’s Republic of ChinaCorrespondence: Yunlong Lou; Heming WuMeizhou People’s Hospital (Huangtang Hospital), No. 63 Huangtang Road, Meijiang District, Meizhou, 514031, People’s Republic of ChinaTel +86 753-2131-591Email louyunlong@mzrmyy.com; wuheming1986@126.comObjective: The present study aimed to investigate the predictive value of some indexes, such as neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), lymphocyte-to-monocyte ratio (LMR), systemic inflammatory response index (SIRI), and systemic immune-inflammatory index (SII) in the survival of nasopharyngeal carcinoma (NPC) and provide reference for the treatment.Methods: A retrospective analysis was performed on 216 patients from 2016 to 2018. The cutoff values of these indexes were determined by the receiver operating characteristic (ROC) curve. The prognostic value of the indexes was evaluated according to the rate of overall survival (OS), regional recurrence-free survival (RRFS), locoregional recurrence-free survival (LRRFS), and distant metastasis-free survival (DMFS).Results: The survival analysis showed that NLR ≤ 2.695 (P = 0.017) and PLR ≤ 140.065 (P = 0.041) were associated with poor OS; however, the LMR and SIRI showed no significant statistical significance. NLR ≤ 2.045 (P = 0.018) and PLR ≤ 125.605 (P = 0.003) were associated with poor RRFS, LMR ≤ 2.535 (P = 0.027) and PLR ≤ 140.065 (P = 0.009) were associated with poor DMFS, NLR ≤ 2.125 (P = 0.018) and PLR ≤ 132.645 (P = 0.026) were associated with poor LRRFS, respectively. Logistic regression analysis showed that low LMR (≤ 2.535) was significantly inferior in OS (HR 23.085, 95% CI 3.425– 155.622, P = 0.001) and DMFS (HR 22.839, 95% CI 4.096– 127.343, P < 0.001). Moreover, low PLR (≤ 140.065) remained significantly related to worse OS (HR 11.908, 95% CI 1.295– 109.517, P = 0.029) and DMFS (HR 9.556, 95% CI 1.448– 63.088, P = 0.019).Conclusion: The index LMR and PLR can be used for predicting survival in NPC patients.Keywords: nasopharyngeal carcinoma, neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, lymphocyte-to-monocyte ratio, systemic inflammatory response index, systemic immune-inflammatory index